2018
DOI: 10.1111/cup.13347
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ulcerative stomatitis: Case series of an under‐recognized entity

Abstract: Chronic ulcerative stomatitis (CUS) is a mucocutaneous condition characterized by chronic relapsing and remitting oral ulcers and erosions. This condition remains under-recognized among dermatopathologists, possibly because of common misdiagnosis as oral erosive lichen planus (LP). We report five cases of CUS in order to raise awareness of this uncommon condition. All patients presented with desquamative gingivitis and/or oral erosions, with biopsies showing lichenoid mucositis and epithelial nuclear IgG depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In fact, there are many similarities between OLP and CUS, both clinically and histopathologically. DIF assays that show a granular or speckled pattern of IgG deposits within or surrounding the nuclei of keratinocytes of basal and parabasal layers of the affected stratified squamous cell epithelium are essential for the diagnosis . In our study, ENS was found in one case each in the OLL and OLDR groups.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In fact, there are many similarities between OLP and CUS, both clinically and histopathologically. DIF assays that show a granular or speckled pattern of IgG deposits within or surrounding the nuclei of keratinocytes of basal and parabasal layers of the affected stratified squamous cell epithelium are essential for the diagnosis . In our study, ENS was found in one case each in the OLL and OLDR groups.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, the lesion showed a good response to a potent topical steroid, fluocinolone acetonide 0.1% in Orabase. In fact, CUS is usually refractory to topical steroids, but improves dramatically when treated with hydroxychloroquine . Another case of a 67‐year‐old woman with OLDR also showed IgG and IgA deposits by ENS with mild intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival lesions manifest in the form of desquamative gingivitis, which is very similar to the clinical appearance of erosive OLP or vesiculobullous diseases (Solomon et al, ). The lesions are usually ulcerative and not preceded by bullae or vesicles, even though a positive Nikolsky's sign has been reported in nine cases in the literature (Beutner et al, ; Chorzelski et al, ; Ko et al, ; Reddy et al, ; Wörle et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other lesions may appear non‐specific: a few patients have shown an asymmetrical distribution and single‐site involvement. In nine cases, vesicles and Nikolsky's sign were observed (Beutner et al, ; Chorzelski et al, ; Ko et al, ; Reddy et al, ; Wörle et al, ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation